In relation to NO-System, Stable Pentadecapeptide BPC 157 Counteracts Lidocaine-Induced Adverse Effects in Rats and Depolarisation In Vitro - Marin Lozic; Vasilije Stambolija; Ivan Krezic; Aleksandra Dugandzic; Gordana Zivanovic-Posilovic; Slaven Gojkovic; Josip Kovacevic; Luka Vrdoljak; Ivan Mirkovic; Antonio Kokot; Andreja Petrovic; Katarina Horvat Pavlov; et al. (Emergency Medicine International)
Recently, the pentadecapeptide BPC 157-induced counteraction of bupivacaine cardiotoxicity has been reported. Medication includes (i) lidocaine-induced local anesthesia via intraplantar application and axillary and spinal (L4-L5) intrathecal block, (ii) lidocaine-induced arrhythmias, (iii) convulsions, and (iv) lidocaine-induced HEK293 cell depolarisation. BPC 157 applications (intraplantar, intraperitoneal, and intragastric) were given (i) immediately after lidocaine, (ii) 10 min after, or (iii) 5 min before. The BPC 157/NO-system relationship was verified with NO-agents, the NOS-blocker L-NAME and the NOS-substrate L-arginine, given alone and/or together, in axillary and spinal intrathecal blocks. BPC 157 applied immediately after lidocaine or 5 min before the application of lidocaine considerably ameliorated plantar presentation. BPC 157 medication considerably counteracted lidocaine-induced limb function failure; L-NAME was counteracted; L-arginine exhibited counteraction when given immediately after lidocaine, but prolongation was seen when given later. Given together, prophylactically or therapeutically, L-NAME and L-arginine (L-NAME + L-arginine) counteracted the other’s response. BPC 157 maintained its original response when given together with L-NAME or L-arginine. When BPC 157 was given together with L-NAME and L-arginine, its original response reappeared. BPC 157 antagonised the lidocaine-induced bradycardia and eliminated tonic-clonic convulsions. Also, BPC 157 counteracted the lidocaine-induced depolarisation of HEK293 cells. Thus, BPC 157 has antidote activity in its own right against lidocaine and local anesthetics.